2020
DOI: 10.3389/fonc.2020.589601
|View full text |Cite
|
Sign up to set email alerts
|

CD44 in Ovarian Cancer Progression and Therapy Resistance—A Critical Role for STAT3

Abstract: Despite significant progress in cancer therapy over the last decades, ovarian cancer remains the most lethal gynecologic malignancy worldwide with the five-year overall survival rate less than 30% due to frequent disease recurrence and chemoresistance. CD44 is a non-kinase transmembrane receptor that has been linked to cancer metastatic progression, cancer stem cell maintenance, and chemoresistance development via multiple mechanisms across many cancers, including ovarian, and represents a promising therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 255 publications
(264 reference statements)
2
35
0
Order By: Relevance
“…It is estimated that 70–80% of patients develop chemoresistance following initial surgery and standardized chemotherapy, although through standardized treatment, patients with OC exhibit favorable perioperative efficacy and prognosis. The development of OC chemoresistance is a complex process involving multiple factors, genes and stages, such as BRAF inhibitors and CD44 ( 28 , 29 ), and severely limits the quality of life and prognosis of patients with OC ( 6 , 30 ). The results of the present study revealed that USP46 expression levels were downregulated in OC chemoresistant tissues compared with chemosensitive tissues, suggesting that abnormal expression of USP46 may be crucial for the development of resistance in OC.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 70–80% of patients develop chemoresistance following initial surgery and standardized chemotherapy, although through standardized treatment, patients with OC exhibit favorable perioperative efficacy and prognosis. The development of OC chemoresistance is a complex process involving multiple factors, genes and stages, such as BRAF inhibitors and CD44 ( 28 , 29 ), and severely limits the quality of life and prognosis of patients with OC ( 6 , 30 ). The results of the present study revealed that USP46 expression levels were downregulated in OC chemoresistant tissues compared with chemosensitive tissues, suggesting that abnormal expression of USP46 may be crucial for the development of resistance in OC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that CD44 and CD117 are two stem cell markers in ovarian cancer, and that CD44 + CD117 + cancer cells present with a powerful survival ability and tumorigenic capability ( 23 , 24 ). In ovarian cancer cells, the overexpression of miR-199a could significantly inhibit CD44 expression and attenuate multidrug resistance and tumorigenicity ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using the correlation between MYB and OC to evaluate the prognosis and explore potential therapeutic targets has attracted much attention [33][34][35].But,the study found that MYB-77867-ES for OC prognosis is favorable AS event. The results suggest that splicing may change the role of genes.AGO2 is a Protein Coding gene, which have effect on cervical cancer, breast cancer and other tumors [36][37][38].AGO2 fail in our study it happened happened AGO2-85285-ES is bene cial to the prognosis of OC, but in other studies, AGO2 can have opposite effects on the prognosis of OC through different pathways [39][40][41].Few studies have been done on SERF1B and ZNF630,we get SERF1B-72406-RI ZNF630-88949-AP close contact with OC, they may be effective prognostic biomarkers and therapeutic targets.Among the remaining results, there are many previous studies on CD44 gene.As a non-kinase transmembrane receptor,CD44 can be used as an effective biomarker to predict the prognosis of OC and negatively affect the outcome of OC [42].CD44 plays a multi-functional role, such as related to cancer stem cells and tumor-associated macrophages, leading to drug resistance of recurrent chemotherapy drugs in OC. It is expected to further dig out effective therapeutic targets to reduce the recurrence rate and drug resistance rate of OC [43,44].It interacts with STAT3 to affect a series of processes such as angiogenesis and immune regulation in OC [45][46][47].CD44 and STAT3 work together on OC in a variety of way,which can provide various ideas for OC treatment.…”
Section: Discussionmentioning
confidence: 99%